Em busca dos sentidos produzidos pelo ato fotográfico na velhice - Vasconcelos, Mário Sérgio [UNESP]; Justo, Joana Sanches (My University, 2012)
Currently the researches that involves working with seniors and their photographs tend to value the return to the past. In this research we intend to follow a different path in order to use the picture for the enhancement of daily life and for prospecting. The objective of the research was to investigate the meanings produced by seniors photographic act about time and memory, emphasizing the possibilities of photography while exploring the future. Photography workshops were conducted with two groups of seniors in the city of Londrina, once a week for 2 months. We noticed that the elderly value more the everyday than the past or the future, as well as friends, family and independence, which were also highlighted in the photographic productions of the groups.

Atualmente as pesquisas que envolvem o trabalho com idosos e suas fotografias tendem a valorizar o retorno ao passado. Nesta pesquisa pretendemos seguir uma caminho diferente, no sentido de utilizar a fotografia para a valorização do cotidiano e para a prospecção. O objetivo da pesquisa foi investigar os sentidos produzidos pelo ato fotográfico na relação do idoso com o tempo e com a memória, dando maior ênfase às possibilidades da fotografia enquanto prospecção do futuro. Foram realizadas oficinas de fotografia com dois grupos de idosos da cidade de Londrina, uma vez por semana, durante 2 meses. Foi possível verificar que os idosos valorizam mais o cotidiano do que o passado ou o futuro, bem como os amigos, a família e a independência, que também tiveram destaque nas produções fotográficas dos grupos.
Searching for the meanings produced by the photographic act in old age
Keywords: Photography; Elderly; Memory; Meaning production; Social psychology; Fotografia; Idoso; Memória; Produção de sentidos; Psicologia social